PENGEMBANGAN E-LKPD MATEMATIKA INTERAKTIF BERBASIS LITERASI DIGITAL - Nazla Nabilla; Sarwo Edy; Fatimatul Khikmiyah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Interactive e-LKPD can be used as a medium for teaching materials that can identify and train digital literacy skills. Interactive E-LKPD is a two-way communication, student worksheets that can perform several activities with feedback with feedback. Social arithmetic is the subject matter studied in junior high school. The subject matter of social arithmetic provides benefits for students in solving problems of daily life, but some students have difficulty solving arithmetic problems. Therefore, this study aims to develop an interactive mathematics E-LKPD based on digital literacy. This type of R and D uses a 4D development model including “Define, Design, Development, and Desseminate”, but limitations without “Disseminate”. The results showed the feasibility of fulfilling several criteria: the validity obtained from the validation results of media experts was 99% and material experts were 95%, the results were both in the "very valid" category. Effectiveness is obtained from the results of class completeness getting 100% "very effective". And the practicality obtained from the results of student responses is 98% "very practical". Thus, the interactive mathematics E-LKPD based on digital literacy can be used as media for teaching materials for the learning process.